The influence of transformational leadership and organizational capital on knowledge management with knowledge sharing as a moderating variable - Ferry Siswadhi (Dinasti Publisher, 2023)
This study is to examine the relationship between Transformational Leadership and Organizational Capital on Knowledge Management, and if this relationship exists and to examine whether Knowledge Sharing has a mediating role in this relationship. The importance and expected contribution of this research is to explain the relationship between Transformational Leadership and Organizational Capital, and to provide new perspectives to employees at the Kerinci District Secretariat and to contribute to previous scientific studies of these variables in a constructive way. To analyze the data, The Structural Equation Modeling (SEM) was used from the AMOS Version 22 statistical software package in modeling and hypothesis analysis. From this research, it was found that Transformational Leadership directly had a better effect on Knowledge Management, and if Transformational Leadership through Knowledge Sharing would weaken Knowledge Management at the Regional Secretariat of Kerinci Regency. Meanwhile, Organizational Capital indirectly through Knowledge Sharing has a better influence on Knowledge Management, in the sense that Organizational Capital through Transformational Leadership can strengthen Knowledge Management at the Regional Secretariat of Kerinci Regency.